Nosocomial and Ventilator-associated Pneumonia - Cabanillas Díez-Madroñero, Carlos; Raboso Moreno, Beatriz; Urrutia-Royo, Blanca; González Muñoz, Imanol; Erro Iribarren, Marta; Pou Álvarez, Cristina; González Gutiérrez, Jessica (Open respiratory archives, 2025)
Nosocomial pneumonia (NP), including its subtype ventilator-associated pneumonia (VAP), represents a major cause of morbidity, mortality, and increased healthcare utilization in hospitalized patients, particularly in intensive care settings. This comprehensive, question-and-answer formatted review synthesizes current evidence on the epidemiology, pathophysiology, and management of NP and VAP, with a focus on multidrug-resistant organisms (MDROs). Key distinctions between NP and VAP are explored in terms of microbiological profiles, diagnostic approaches, and therapeutic implications. The review provides a detailed analysis of risk factors for MDROs – including prolonged mechanical ventilation, prior antibiotic exposure, and host-related immunosuppression – emphasizing the importance of risk stratification in guiding empirical antibiotic selection. A critical appraisal of international guideline recommendations (IDSA/ATS, ERS, SEPAR) highlights areas of consensus and divergence, particularly regarding empirical treatment strategies and the role of narrow- versus broad-spectrum coverage. The integration of rapid molecular diagnostic tools, such as multiplex PCR, is discussed in depth, including their potential to improve diagnostic yield, facilitate early de-escalation, and enhance antimicrobial stewardship. Recent advances in antimicrobial development are reviewed, covering novel β-lactam/β-lactamase inhibitor combinations and siderophore cephalosporins with activity against ESBL−, KPC−, and carbapenemase-producing pathogens. Their appropriate use in critically ill patients is contextualized within the framework of pharmacokinetic/pharmacodynamic optimization. Finally, the review examines current evidence on treatment duration, supporting a 7–8 day course in most cases, with individualized extension in selected high-risk populations. The utility of procalcitonin as a biomarker to guide antibiotic discontinuation is also addressed. This review provides clinicians with a concise, evidence-based reference to inform the complex decision-making required in managing nosocomial pneumonia in the era of antimicrobial resistance. La neumonía nosocomial (NN), incluyendo su subtipo la neumonía asociada a ventilación mecánica (NAVM), constituye una de las principales causas de morbilidad, mortalidad y aumento de los costes sanitarios en pacientes hospitalizados, especialmente en unidades de cuidados intensivos. Esta revisión, presentada en un formato de preguntas y respuestas, sintetiza la evidencia actual sobre la epidemiología, fisiopatología y manejo de la NN y la NAVM, con especial atención a los patógenos multirresistentes (PMR). Se analizan las diferencias clave entre la NN y la NAVM en cuanto a perfil microbiológico, estrategias diagnósticas e implicaciones terapéuticas. Se detallan los principales factores de riesgo para infecciones por PMR—como la ventilación prolongada, la exposición previa a antibióticos y la inmunosupresión—, destacando la necesidad de una estratificación individualizada del riesgo para guiar el tratamiento empírico. Se revisan críticamente las recomendaciones de las principales guías internacionales (IDSA/ATS, ERS, SEPAR), resaltando coincidencias y discrepancias, especialmente en cuanto al uso de tratamientos empíricos de amplio o estrecho espectro. Asimismo, se discute el papel de las técnicas diagnósticas moleculares rápidas, como la PCR múltiple, en la mejora del rendimiento diagnóstico y la optimización del uso de antimicrobianos. Se incluye un análisis actualizado de los nuevos antibióticos disponibles frente a PMR, contextualizado en pacientes críticos, y se revisa la evidencia que respalda pautas abreviadas de 7-8 días en pacientes con buena evolución clínica. Finalmente, se aborda la utilidad de la procalcitonina como biomarcador para orientar la suspensión del tratamiento antibiótico.